A Study of the Diagnostic Accuracy of an Existing Multivariable Test to Predict Shoulder Dystocia - Easley, Henry Alexander, III; Beste, Todd Michael (American Journal of Perinatology Reports, 2019)
Objectives To evaluate the diagnostic accuracy of a multivariable prediction model, the Shoulder Screen (Perigen, Inc.), and compare it with the American College of Obstetricians and Gynecologists (ACOG) guidelines to prevent harm from shoulder dystocia.Study Design The model was applied to two groups of 199 patients each who delivered during a 4-year period. One group experienced shoulder dystocia and the other group delivered without shoulder dystocia. The model's accuracy was analyzed. The performance of the model was compared with the ACOG guideline.Results The sensitivity, specificity, positive, and negative predictive values of the model were 23.1, 99.5, 97.9, and 56.4%, respectively. The sensitivity of the ACOG guideline was 10.1%. The false-positive rate of the model was 0.5%. The accuracy of the model was 61.3%.Conclusion A multivariable prediction model can predict shoulder dystocia and is more accurate than ACOG guidelines.
Keywords: shoulder dystocia; brachial plexus injury; prediction; medicolegal